132k views
2 votes
Please can you give me the answers to the questions above in standard form.​

Please can you give me the answers to the questions above in standard form.​-example-1
User Thmsn
by
5.8k points

1 Answer

4 votes

Answer:

a)
4.5 * 10^(11)

b)
3.5 * 10^(3)

Explanation:

a) We have to simplify the below expression in standard form.

The expression is
(5* 10^(3)) * (9 * 10^(7))

Now,
(5* 10^(3)) * (9 * 10^(7))

=
(9 * 5) * (10^(3) * 10^(7))

=
45 * 10^((3 + 7)) {Since
a^(b) * a^(c) = a^((b + c))}

=
45 * 10^(10)

=
4.5 * 10^(11) (Answer)

b) We have to simplify the below expression in standard form.

The expression is
(7* 10^(5)) / (2 * 10^(2))

Now,
(7* 10^(5)) / (2 * 10^(2))

=
(7 / 2) * (10^(5) / 10^(2))

=
3.5 * 10^((5 - 2)) {Since
a^(b)/ a^(c) = a^((b - c))}

=
3.5 * 10^(3) (Answer)

User Azjezz
by
5.6k points